2003
DOI: 10.1007/s00787-003-0334-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexually abused girls: patterns of psychopathology and exploration of risk factors

Abstract: This paper studies the patterns of psychopathology in sexually abused girls. It also explores some environmental risk factors for psychopathology including abuse characteristics and environmental experiences. The data are derived from the baseline assessment of 81 sexually abused girls referred to the London Child Sexual Abuse Psychotherapy Outcome Study (collaborative Tavistock and Maudsley project). Data about abuse were collected from the parent or foster parent using a standardised, semi-structured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similar findings have been reported before, for example, Sadowski et al . () found that a longer time frame between the last CSA experience and assessment was a significant predictor of depression. These results seem to imply that the long‐term effect of CSA is more prominent than the short‐term effect, and with an adult sample, more consistent findings could be observed across studies.…”
Section: Discussionmentioning
confidence: 96%
“…Similar findings have been reported before, for example, Sadowski et al . () found that a longer time frame between the last CSA experience and assessment was a significant predictor of depression. These results seem to imply that the long‐term effect of CSA is more prominent than the short‐term effect, and with an adult sample, more consistent findings could be observed across studies.…”
Section: Discussionmentioning
confidence: 96%
“…Egelund and Lausten, 2009), which do not capture specific dimensions of PTSD symptomatology. Prevalence rates of PTSD in looked after children range from 22 per cent (Chambers et al, 2010) to 71 per cent (Sadowski et al, 2003). Interestingly, in the Sadowski study, PTSD was the most highly prevalent of all reported mental health problems, with 67 per cent of children reporting depression, 62 per cent separation anxiety, 38 per cent general anxiety, 33 per cent social phobia and 29 per cent reactive attachment disorder.…”
Section: Ptsd In Looked After Childrenmentioning
confidence: 99%
“…High levels of mood disorders, such as major depressive episodes, are found in cohorts of children and teenagers who have been sexually abused [56,57]. Sexually abused children are more likely than their non-abused counterparts to present behavior problems, such as inappropriate sexualized behaviors [58].…”
Section: Mental Health Outcomes: What Are the Effects Of Csa?mentioning
confidence: 99%